Pengaruh Knowledge Sharing terhadap Perilaku Inovatif pada Pengurus Organisasi Mahasiswa (Studi pada Pengurus Organisasi Mahasiswa Fakultas Ekonomi dan Bisnis UBP Karawang Periode 2022-2023) - Ricky Prayoga; Enjang Suherman; Zenita Apriani (Departement of Mathematics Education, 2023)
This study aims to determine the effect of Knowledge Sharing on the innovative behavior of the management of the student organization of the Faculty of Economics and Business, Buana Perjuangan University, which still has the task of increasing the ability of its administrators to be able to support national scale academic achievements that can be obtained by student organizations of the Faculty of Economics and Business. Buana Perjuangan University, Karawang, this research is aimed at organizational management of the Faculty of Economics and Business from the period 2021 to 2023. The research method used is quantitative descriptive verification. The total population in this study is all administrators of student organizations for the period 2022-2023. Faculty of economics and business, Buana University. Karawang struggle, amounting to 85 students. This study used the Slovin formula in determining the research sample with a total of 70. Based on the results and discussion in this study, it can be concluded as follows: the knowledge sharing category in student organizations is at a good level and innovative behavior has a good category. The influence of Knowledge sharing which is an activity in the circulation of information within the organization has a good effect on the innovative behavior of student organizations of the Faculty of Economics and Business at Buana Perjuangan University, in this case knowledge sharing is an important activity in organizations that includes aspects of human resource development in the organization. with the emergence of innovative behaviors from student organization administrators in organizational progress and the progress of Buana Perjuangan University.